Perfil da terminologia dos documentos escolares individuais - Assumpção, Glória de Fátima Pinotti de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Academic documents are of great importance to society due to the fact that they are useful for consultation and demonstration of the educational and professional profile of candidates who go through selection processes for various reasons. The purpose of this doctor's thesis is to describe the terminology profile of Personal Academic Documents, in a text-based body of work in Brazilian Portuguese, analyzing organizational aspects from the morphosyntactic and lexical-semantic points of view. The choice of this topic is related to the fact that this terminology is the base for several socio-professional activities in the educational environment and in services and industry, and can also contribute to the development of consulting and translation knowledge. Based on a reading of public notices, we can see that candidates who go through selection processes provide personal documents, including those which contribute to a distinct profile: Minutes, affidavits, notices, certifications, certificates, declarations, diplomas, registration cards, academic transcripts, honorable mentions and requirements. We describe these as personal academic documents. One hundred and sixty-nine documents issued by public and private teaching establishments throughout the country were analyzed for this research. Using the Concordance computer tool we extracted concordance lists from the units, by type of document, totaling 2,847 candidate terms. For each unit, we took the context of use into account using a special bibliography composed of specific legislation and technical manuals. We also considered other criteria such as area identity, the formality of the written text and employability of use, among others traditionally used in research of this nature. We considered 452 units representative of the domain of the personal academic documents, including simple, complex and composite terms. We based our work on the theoretical fundamentals of Cabré's ...

Os documentos escolares são de grande importância na sociedade pelo fato de servirem para consultas e constatações acerca do perfil escolar e profissional de candidatos que se submetem a processos seletivos para fins diversos. O objetivo desta tese de doutoramento é descrever o perfil da terminologia dos Documentos Escolares Individuais, num corpus de base textual em Português do Brasil, analisando aspectos da organização sob o ponto de vista morfossintático e léxico-semântico. A escolha desse tema está relacionada ao fato dessa terminologia ser a base para vários atividades socioprofissionais, no ambiente educacional, em serviços e indústria e também poder contribuir para a formação do conhecimento de consulentes e traduções. A partir da leitura de editais, percebemos que os candidatos que se submetem a processos seletivos entregam documentos pessoais, dentre os quais, aqueles que contribuem para a constituição de um perfil diferenciado: atas, atestados, boletins, certidões, certificados, declarações, diplomas, fichas de matrícula, históricos escolares, menções honrosas e requerimentos. Denominamos este conjunto de documentos escolares individuais. Nesta pesquisa foram analisados cento e sessenta e nove documentos, expedidos por estabelecimentos de ensino públicos e particulares, localizados em todo território nacional. Com o auxílio da ferramenta computacional Concordance, procedemos a extração das unidades em listas de concordância, por tipo de documento, totalizando 2.847 candidatos a termos. Para cada unidade, levamos em conta o contexto de uso em uma bibliografia especializada composta de legislação específica e manuais técnicos. Consideramos também outros critérios como pertencimento na área, formalidade dos textos escritos, empregabilidade de uso, entre outros tradicionalmente empregados em pesquisas dessa natureza. Consideramos representativos do domínio dos documentos escolares individuais...
Keywords: Socioterminologia; Documentos Escolares Individuais